2016
DOI: 10.1080/07391102.2016.1204945
|View full text |Cite
|
Sign up to set email alerts
|

Molecular modeling study for the design of novel acetyl-CoA carboxylase inhibitors using 3D QSAR, molecular docking and dynamic simulations

Abstract: Acetyl-CoA carboxylase (ACC) enzyme plays an important role in the regulation of biosynthesis and oxidation of fatty acids. ACC is a recognized drug target for the treatment of obesity and diabetes. Combination of ligand and structure-based in silico methods along with activity and toxicity prediction provides best lead compounds in the drug discovery process. In this study, a data-set of 100 ACC inhibitors were used for the development of comparative molecular field analysis (CoMFA) and comparative molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…At room temperature, the kinetic energy was reduced from 685.88 kcal/mol to 386.34 kcal/mol, while at 4C it was reduced from 633.64 kcal/mol to 370.61 kcal/mol. The kinetic energy is known to be reduced at lower temperatures, resulting in reduced free energy and hence a more stable complex (Vyas et al 2017). These results were in line with those obtained from the stability study, which showed that the VCM_NMEO SLNs were more stable when stored at 4 °C in terms of PS, PDI and ZP (Table 4).…”
Section: Molecular Modellingmentioning
confidence: 99%
“…At room temperature, the kinetic energy was reduced from 685.88 kcal/mol to 386.34 kcal/mol, while at 4C it was reduced from 633.64 kcal/mol to 370.61 kcal/mol. The kinetic energy is known to be reduced at lower temperatures, resulting in reduced free energy and hence a more stable complex (Vyas et al 2017). These results were in line with those obtained from the stability study, which showed that the VCM_NMEO SLNs were more stable when stored at 4 °C in terms of PS, PDI and ZP (Table 4).…”
Section: Molecular Modellingmentioning
confidence: 99%